Influence of urban air pollution on the population in the Klang Valley, Malaysia: a spatial approach - Mohd Shafie, Siti Haslina; Mahmud, Mastura; Mohamad, Suzani; Rameli, Nor Lita Fadilah; Abdullah, Ramdzani; Mohamed, Ahmad Fariz (Ecological processes, 2022)
Background Urban air pollution resulting from economic growth as well as urbanization impacts the health of inhabitants. This study aims to examine the spatial distribution of particulate matter (PM 10 ) and the risk of exposure for the population in the Klang Valley, an urban conglomeration centred in Kuala Lumpur, Malaysia. Methods The inverse distance weighted (IDW) interpolation technique in the ArcGIS platform was used to map the air quality from five air monitoring stations. Spatial statistics of the Global Moran’s I Spatial Autocorrelation and Optimized Hot Spot Analysis were used to estimate the spatial clustering of PM 10 . The population-weighted exposure level (PWEL) technique was used to calculate the population density susceptible to PM 10 and the AirQ+ model was applied to estimate the proportion of the adult population at risk of chronic bronchitis due to long-term exposure to PM 10 concentrations in the Klang Valley. Results The highest annual mean PM 10 concentrations at the Klang station ranged between 80 and 100 μg/m 3 from 2000 to 2009 and exceeded the New Malaysia Ambient Air Quality Standard (NMAAQS) and the World Health Organization Air Quality Guidelines (WHOAQG) levels of 40 and 20 μg/m 3 , respectively. The Moran's I results indicated that the statistically significant clusters of high PM 10 in Klang present a health risk to the local community. The PWEL results showed that levels of PM 10 in Petaling Jaya exceeded the WHOAQG limits, potentially posing a health risk to the high-density population. The AirQ+ model found Klang to be a significantly high-risk area for chronic bronchitis among the adult population with 804,240 people (with a relative risk of 1.85) in 2009. Conclusion These high-risk values are due to rapid urbanization and high motor vehicle usage in the Klang Valley and therefore the impact of PM 10 on the population needs to be reduced. This situation should be taken seriously by the Department of Environment and Kuala Lumpur City Hall in addressing air pollution issues through stricter rules on emissions and implementing low-carbon policies to improve the well-being of residents.